An analysis of didactic resources as alternatives for teaching Mathematics from the perspective of Inclusive Education - Macedo, Shirley da Silva; Santos, Maria Gabriela Pereira dos; Carmo, Raquel Alves Martins do (Educação Matemática Debate, 2023)
This work is a compilation of some texts on inclusion and practical Mathematics activities from the perspective of Inclusive Education. It aims to analyze the positive influence of these activities as possible teaching resources for students with disabilities. To this end, we achieved a historical analysis with reference to inclusion based on theoretical arguments and laws. We observed that planning the elaboration and development of the proposed mathematical activities is fundamental to facilitate the learning of the contents, respecting the student’s specificities. We identified from the analysis of the documents studied, the importance of teaching resources in Mathematics classes and their positive interference in the students learning belonging to the target audience of Special Education.